Model Pembelajaran Kooperatif Tipe STAD dan Hasil Belajar Matematika Siswa SMA - Muhammad Diennis Dwi Mustika; Lula Denanda Putri Mustiayu; Laelin Fakhriyani; Khofifah Indra Prawangsa (Pendidikan Matematika FKIP Universitas Mataram, 2023)
Education is a systematic learning process that aims to develop individual abilities in all aspects of life. One of the important subjects in education is mathematics. To achieve maximum math learning outcomes, an effective and efficient learning model is needed. There are various kinds of math learning models that can be used, such as cooperative learning models, inquiry learning models, and so on. The purpose of this study was to determine the STAD type cooperative learning model and math learning outcomes. The research method used in this study is the SLR (Systematic Literature Review) method. Data collection is done by documenting all articles that have similar research in the research report. The articles used in this study were 20 journal articles and Scopus indexed proceedings using the Publish or Perish application. The results showed that the STAD type cooperative learning model was able to improve student learning outcomes.